Pengaruh Minat Belajar Terhadap Hasil Belajar pada Mata Pelajaran Seni Budaya Siswa Kelas XI Di SMA Negeri 3 Payakumbuh - Wadania Sagita Devi; Fuji Astuti (SENDRATASIK UNP, 2023)
This1study1aims to1determine the influence of learning interest on the learning outcomes of class XI1students on the subject of cultural arts of class XII students at SMA Negeri 3 Payakumbuh. This type of research is quantitative research. The population in this study was 320 students1of1class1XI SMA Negeri 3 Payakumbuh with a sample of 76 students. The data in this study used primary data and1secondary1data. Data1collection techniques are carried out by means of questionnaires, learning outcomes data. Variables in this study consist of Free Variables (Independent Variables) and Bound Variables (dependent Variables). Data analysis techniques are carried out with validity tests and reliability tests. The1results1showed that there was an influence of interest in learning on learning outcomes in the subject of cultural arts of class XI students at SMA Negeri 3 Payakumbuh. It is known that the calculated F value is 45.663 while the Ftabel is 3.97. Because Fhitung > Ftabel means, that the variable of interest in learning affects student learning outcomes. Based on the Determinant Coefficient (R2) table, an R2 value of 0.382 was obtained, which means that learning interest can affect learning outcomes with strength as much as 38.2% while the other 61.8% of learning interest is influenced by other variables that are not measured in this study. That is, the level of interest in learning students affects learning outcomes. Based on the Determinant Coefficient (R2) table, an R2 value of 0.382 was obtained, which means that learning interest can affect learning outcomes with strength as much as 38.2% while the other 61.8% of learning interest is influenced by other variables that are not measured in this study. That is, the level of interest in learning students affects learning outcomes. Based on the results of data analysis obtained through regression calculations, it can be concluded that the learning interest variable contributes 38.2% to changes in student learning outcome variables while the remaining 61.8% is influenced by other factors. The variable interest in learning, which contributes 38.2% to student learning outcomes, is a sufficient but still relatively low result.